Marine algae of British Columbia and Northern Washington. Part I Chlorophyceae (green algae). - Scagel, Robert F. (Department of the Secretary of State, 1966)
Bulletin (National Museum of Canada) ; no. 207.Bulletin (National Museum of Canada). Biological series ; no. 74.